Electrochemical and computational investigation of Cicer arietinum extract as renewable and environmentally green corrosion inhibitor for aluminium in acidic environment - Hala. M. Hassan (Scientific Reports)
Abstract This study investigates the potential of Cicer arietinum extract (CAE) as a cost-effective and environmentally friendly solution to prevent aluminum (Al) corrosion in acidic environments. This study aimed to identify a cost-effective and environmentally friendly corrosion inhibitor for aluminum. The effectiveness of CAE as a novel and environmentally safe inhibiting aluminum corrosion in a 1 M hydrochloric acid solution was evaluated using weight loss measurements (WL), potentiodynamic polarization (PDP), and electrochemical impedance spectroscopy (EIS). The surface morphology of Al that was corroded in the test solution was further investigated using atomic force microscopy (AFM) and scanning electron microscopy (SEM). Analysis of inhibition efficiency and kinetic data revealed the adsorption mechanism and isotherm type. The advantages of CAE include its non-toxicity, environmental friendliness, ease of preparation, and contain (O, P, and π-Bonds). The experiments showed that adding 150 ppm of CAE at 298 K resulted in an inhibition efficiency of approximately 91.1%. While increasing inhibitor concentration improved protection efficiency, higher temperatures reduced its effectiveness. The calculated low negative values of Gibbs free energy of adsorption (ΔG ad) (− 23.2, − 22.5, − 21.9, and − 21.7 kJ mol−1) from the Langmuir isotherm suggest that CAE adsorbs onto the aluminum surface through a physisorption mechanism. Further electrochemical studies, such as polarization techniques, are recommended to further elucidate the corrosion inhibition mechanism. The polarization curves suggest that CAE acts as a mixed-type inhibitor. Applying CAE as a protective inhibitor to metal surfaces can significantly reduce the risk of corrosion in industrial practices. Furthermore, the Density Functional Theory (DFT) method determined the quantum chemical parameters. The inhibition mechanism of Al in the aggressive solution was elucidated through a combination of experimental data, DFT calculation, and surface analysis.